Analysis of Factor Affecting Frequency Coupling of Double Planetary Gear System - Hao Xiaohua; Yuan Xia; Bai Jinlin; Li Fenggang; Qin Jin (Jixie chuandong)
Aiming at the phenomenon of frequency coupling in the dynamic response of double planetary gears system，this paper uses MSC.Adams software to establish a dynamic simulation models for two typical connection forms of double planetary gears system. The meshing force is Fourier-decomposed and combined according to the two-row tooth frequency and its multiplication. The influence of joint stiffness，rotational speed and load on frequency coupling of double planetary gears is studied by the ratio of the amplitude of the two-part meshing force. The results show that when the joint stiffness of the connection shaft reaches 108 N·mm/（°） or more，the proportion of frequency coupling is stable，and the current gear tooth frequency influence ratio is always higher than the coupling gear frequency influence ratio. As the speed increases，the current gear tooth frequency influence ratio increases，and the load increases，the current gear tooth frequency influence ratio decrease，the coupling frequency influence ratio is opposite. For the parallel tooth row load and speed combination analysis，in the working range，the frequency coupling influence ratios in the two rows are similarly expressed，∑fh minus∑fb is proportional to the load ratio minus the speed ratio. In multi-row planetary gear system，the frequency influence ratio distribution conforms to the above-mentioned frequency coupling law of series and parallel row，and the frequency coupling of parallel row is more serious than that of series row.